Modeling developmental changes in the yo-yo intermittent recovery test level 1 in elite pubertal soccer players - Deprez, D.; Valente-dos-Santos, J.; Coelho e Silva, M.; Lenoir, M.; Philippaerts, R. M.; Vaeyens, R. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To model the development of soccer-specific aerobic performance, assessed by the Yo-Yo Intermittent Recovery Test Level 1 in 162 elite pubertal soccer players, age 11-14 y at baseline. Methods: Longitudinal multilevel modeling analyses comprised predictors related to growth (chronological age, body size [height and weight] and composition [fat mass, fat-free mass]), and motor coordination [3 Körperkoordination Test für Kinder subtests: jumping sideways, moving sideways, backward balancing] and estimated biological-maturation groups (earliest [<percentile 33] and latest maturers [>percentile 66]). Results: The best-fitting model on soccer-specific aerobic performance could be expressed as -3639.76 + 369.86 × age + 21.38 × age2 + 9.12 × height - 29.04 × fat mass + 0.06 × backward balance. Maturity groups had a negligible effect on soccer-specific aerobic performance (-45.32 ± 66.28; P > .05). Conclusion: The current study showed that the development of aerobic performance in elite youth soccer is related to growth and muscularity and emphasized the importance of motor coordination in the talent-identification and -development process. Note that biological maturation was excluded from the model, which might endorse the homogeneity in estimated biological-maturation status in the current elite pubertal soccer sample.